Comparison of the seventh and eighth editions American Joint Committee Cancer classification system in oral cavity squamous cell cancers - Singhavi, Hitesh Rajendra; Chakrabarti, Swagnik; Singh, Arjun; Mair, Manish; Bhattacharjee, Atanu; Shetty, Rathan; Qayyumi, Burhanuddin; Pai, Ameya; Joshi, Poonam; Nair, Deepa; Nair, Sudhir; Chaturvedi, Pankaj (International journal of cancer, 2020)
The aim of our study was to evaluate the predictive ability of the American Joint Committee Cancer (AJCC) eighth edition (AJCC8) staging system for oral cavity cancers and validate these changes rendering the hypothesis of improving prognostication. We conducted a retrospective study including all oral cavity squamous cell carcinoma patients visiting our tertiary center from 2012 to 2015, staged as per the AJCC seventh edition (AJCC7) and AJCC8 systems. Stage‐specific disease‐free survival (DFS) and overall survival (OS) were calculated using the Kaplan‐Meier method. Concordance index (CI) and Akaike information criterion (AIC) were used to calculate the predictive accuracy of the both systems. The study sample consisted of 863 subjects followed up for a median of 24 months. Buccal mucosa complex (BMC) was the most common site (n = 496). We observed a 25.8% (n = 222) overall upstaging in the eighth edition, significantly seen in early tongue cancers (TCs) (Stage I) and advanced BMC cancers (Stage III). An increase in CI and reduction in AIC scores were indicative of a superior predictive accuracy for the eighth edition in assessing DFS (confidence interval [CI*] = 0.650–0.654; AIC = 3,022–3,014) and OS (CI* = 0.643–0.648; AIC = 2089–2086) across all stages. The accuracy was higher for TCs as compared to BMC. Although not statistically significant, we observed an increase in soft risk factors at higher stages in the eighth edition as compared to its predecessor. We concluded that the AJCC8 has a higher predictive accuracy than the AJCC7 edition, making it a reliable prognosticative tool. What's new? The American Joint Committee Cancer (AJCC) 8th edition staging system recently incorporated tumor depth of invasion and extranodal extension as two major prognostic factors. The true global impact of these changes on stage distribution and prognosis remains unknown, however, particularly in oral cancer. This retrospective study conducted in India included 863 patients staged as per the 7th and 8th edition systems with a median 24 month‐follow‐up. Overall, 25.8% patients underwent upstaging as per the new classification system. Patients with upstaged disease had poorer survival outcomes. The 8th edition staging system had higher accuracy in predicting outcomes among oral cancer patients.